Evolutionary and ecological insights into the emergence of arthropod-borne viruses - Marklewitz, Marco; Junglen, Sandra (Acta tropica, 2019)
The emergence of arthropod-borne viruses (arboviruses) is of global concern as they can rapidly spread across countries and to new continents as the recent examples of chikungunya virus and Zika virus have demonstrated. Whereas the global movement patterns of emerging arboviruses are comparatively well studied, there is little knowledge on initial emergence processes that enable sylvatic (enzootic) viruses to leave their natural amplification cycle and infect humans or livestock, often also involving infection of anthropophilic vector species. Emerging arboviruses almost exclusively originate in highly biodiverse ecosystems of tropical countries. Changes in host population diversity and density can affect pathogen transmission patterns and are likely to influence arbovirus emergence processes. This review focuses on concepts from disease ecology, explaining the interplay between biodiversity and pathogen emergence.